Anarchic solidarity autonomy, equality, and fellowship in Southeast Asia - Gibson, Thomas 1956-; Sillander, Kenneth (Monograph / Yale Southeast Asia Studies, 2011)
"This volume analyzes a group of Southeast Asian societies that have in common a mode of sociality that maximizes personal autonomy, political egalitarianism, and inclusive forms of social solidarity. Their members make their livings as nomadic hunter-gatherers, shifting cultivators, sea nomads, and peasants embedded in market economies. While political anarchy and radical equality appear in many societies as utopian ideals, these societies provide examples of actually existing, viable forms of "anarchy." This book documents the mechanisms that enable these societies to maintain their life-ways and suggests some moral and political lessons that those who appreciate them might apply to their own societies"--Back cover.